Pengaruh Emotional Intelligence Terhadap Work Peformance Pada Rutan Kelas IIB Prabumulih - M Satrio Gadang Kuncoro; Padmono Wibowo (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to identify and analyze the effect of emotional intelligence on the job performance of Rutan Kelas IIB Prabumulih staff. The approach used in this study is a quantitative approach. The research population included all officers of the Rutan Kelas IIB Prabumulih and a sample of 31 people was taken using the Random Sampling method. Collecting data from this study using a questionnaire. The data analysis technique used the analysis requirements test, simple linear regression test and also the f test with non-parametric statistics, as well as processing of the existing data in this study using the IBM SPSS statistics software program version 2.2. The results of this study have proven that Ho is rejected and Ha is accepted with a significance value (sig) of 0.002. This value is said to affect because the value is 0.002 <005. Thus emotional intelligence has a significant effect on the Job performance of Rutan Kelas IIB Prabumulih employees.